Partisipasi Masyarakat Dalam Pengembangan Ekowisata Memancing di Desa Rantau Baru, Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan, Provinsi Riau - Nofrizal Nofrizal; Rommie Jhonnerie; Alit Hindri Yani; Bustari Bustari; Riska Fatmawati; Ramses Ramses; Imam Arifandy; Rahmadi Rahmadi (CANANG: Jurnal Pengabdian Masyarakat, 2022)
Community service activities regarding community participation in the development of fishing ecotourism involve Rantau Baru Village officials, traditional leaders and stakeholders, fishing communities, traders in Rantau Baru Village, Tourism Office, Fisheries Service of Pangkalan Kerinci Regency, Pelalawan Regency. The number of participants who were involved in this activity is 23 people. Fishermen in Rantau Baru Village were selected by 5 people per hamlet. While the traders who will be involved are 10 people consisting of day traders and fish collectors who always do business in Rantau Baru Village. A location survey was conducted to determine the number of people who work as traditional fishermen and businessmen (traders) in Rantau Baru Village. At the same time to record fishermen who are already involved and who have not been involved in fishing tourism activities. Furthermore, the survey was conducted to coordinate with the tourism and fisheries services in Pelalawan Regency, Riau Province. This counseling is addressed to a number of stakeholders that have been determined. Selection of stakeholders based on direct involvement with fishing tourism activities and also those who have the potential to develop and invest in the provision of facilities and infrastructure to support fishing tourism activities. The implementation of the activity will be carried out at the Rantau Baru Village Office, Pangkalan Kerinci District, Pelalawan Regency, Riau Province. Furthermore, this activity will also involve tourists who always visit Rantau Baru Village to get opinions regarding their needs and convenience while carrying out fishing tourism activities. The results of the activity showed that the community service activities went well which was attended by 23 participants who work as fishermen and staff of the Fisheries and Maritime Service, Pelalawan Regency. The success of this service activity is indicated by the results of the post test and the responses of the participants. Most of the participants were very enthusiastic and interested in being involved in this fishing ecotourism activity. Some of the participants who owned pompong boats, robin boats and rowing boats also wished to become tourist guides for fishing tourism activities. The participation and enthusiasm of the participants was very good for this activity. This is indicated by the perception, response and evaluation of this activity by using a preliminary test and a posttest. Most of the participants felt interested in presenting material about community participation in the development of fishing ecotourism. The participants' understanding of the material was also very good, this indicated that most of the participants really understood and understood the strategies for developing fishing ecotourism. Apart from that, there was a lot of input in the form of the hopes of all parties, such as the local government, related agencies, regional heads, investors and the university to be involved in the development of fishing tourism in Rantau Baru Village. Improving the facilities and infrastructure to support fishing tourism is also a demand in the future to be able to implement fishing ecotourism activities in Rantau Baru Village. Fishing ecotourism activities are supported by facilities and infrastructures, therefore it is necessary to provide lodging, communication (Telkomsel tower) restaurants, shops selling fishing tackle and bait, information facilities, security and health facilities. In addition, in implementing the development of fishing ecotourism, it is necessary to carry out promotion, community participation and support from all parties.